A veia ázigos direita na cutia (Dasyprocta aguti, rodentia) - OLIVEIRA, Paola Franssinetti Nunes Machado; CARVALHO, Maria Acelina Martins; SOUZA, Wilson Machado [UNESP]; MIGLINO, Maria Angélica (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 1999)
O comportamento da veia ázigos, sua formação e topografia foram estudados em 10 cutias (Dasyprocta aguti, rodentia) adultas (6 machos e 4 fêmeas, capturadas no estado do Piauí, Brasil). Este trabalho tem por objetivo constituir a base de outras investigações, particularmente aquelas referentes à exploração zootécnica desta espécie. O sistema de veia ázigos foi injetado com látex - Neoprene 671, e os animais foram colocados em solução aquosa de formol a 10%, e dissecados. em todas as espécies foi observado que a veia ázigos sempre chega na veia cava cranial em nível do quarto espaço intercostal. A veia ázigos recebe em (50%) dos casos as veias intercostais à direita e (50%) à esquerda. As tributárias da veia ázigos são: as veias frênicas (100%) e a veia bronco esofágica (30%). A veia hemiázigos aparece em todos os casos à esquerda e em 60% dos casos à direita. A veia ázigos comunica-se com a veia hemiázigos esquerda (90%), e com a direita (100%), com a veia cava caudal e veias intervertebrais, com igual freqüência (30%).

The behaviour of the azygos vein, its formation and topography were studied in 10 cutias (Dasyprocta aguti, rodentia) adults (6 males and 4 females) captured in the State of Piauí, Brazil. This research intends to be a base for other investigations, particularly those with reference to zootechnical exploration of this species. The azygos venous system was injected with latex (Neoprene 671), then the animals were put in watery solution of formol 10%, and dissected. In all specimens it was observed that the azygos vein always arrives in the cranial vena cava on a level with fourth intercostal space. The azygos vein receives more frequently (50%), the intercostal veins on the right side and 5 (50%) on the left one. The tributaries of the azygos vein are the phrenic veins (l00%), and the broncoesophagea vein (30%). The hemiazygos vein is in all cases on the left side and in 60% of the cases on the right side. The azygos vein communicates with the left hemiazygos vein (90%), with the right one (100%), and with the vena cava caudal and intervertebral veins, with equal frequency (30%).
The right azygos vein in agouti (Dasyprocta aguti, rodentia)
Keywords: Roedores; Cutias; Veias; Rodents; Agouti; Veins